Ternary Platinum–Copper–Nickel Nanoparticles Anchored to Hierarchical Carbon Supports as Free-Standing Hydrogen Evolution Electrodes - Shen, Yi (2017)
Developing cost-effective and efficient hydrogen evolution reaction (HER) electrocatalysts for hydrogen production is of paramount importance to attain a sustainable energy future. Reported herein is a novel three-dimensional hierarchical architectured electrocatalyst, consisting of platinum–copper–nickel nanoparticles-decorated carbon nanofiber arrays, which are conformally assembled on carbon felt fabrics (PtCuNi/CNF@CF) by an ambient-pressure chemical vapor deposition coupled with a spontaneous galvanic replacement reaction. The free-standing PtCuNi/CNF@CF monolith exhibits high porosities, a well-defined geometry shape, outstanding electron conductivity, and a unique characteristic of localizing platinum–copper–nickel nanoparticles in the tips of carbon nanofibers. Such features render PtCuNi/CNF@CF as an ideal binder-free HER electrode for hydrogen production. Electrochemical measurements demonstrate that the PtCuNi/CNF@CF possesses superior intrinsic activity as well as mass-specific activity in comparison with the state-of-the-art Pt/C catalysts, both in acidic and alkaline solutions. With well-tuned composition of active nanoparticles, Pt42Cu57Ni1/CNF@CF showed excellent durability. The synthesis strategy reported in this work is likely to pave a new route for fabricating free-standing hierarchical electrodes for electrochemical devices.